Stagnation or Revival : Israeli Disengagement and Palestinian Economic Prospects - World Bank (Washington, DC, 2013)
The World Bank's June 23 report, "Disengagement, the Palestinian Economy and the Settlements," warns of the potential disintegration of the Palestinian economy under the sustained pressures of conflict and Israeli closure policies--a situation which is potentially ruinous for both Palestinians and Israelis. Currently there is hope that the Israeli and Palestinian governments are once again ready to discuss their shared future. At this juncture, it is vital that policy-makers focus on stabilizing and reviving the economy as part of any new political process. While money, and in particular donor money, has an important role to play, the underlying causes of economic decline need to be addressed. For a recovery to take place, the Government of Israel needs to roll back the system of restrictions on the movement of people and goods imposed since the beginning of the intifada - it is these various closure measures that are the proximate cause of four years of Palestinian economic distress. The Government of Israel has given encouraging signs of a willingness to reform the management of border gateways, to enable a much faster and more reliable throughput of cargo and people. For its part, the Palestinian Authority faces two sets of challenges if it is to play its part in bringing about revival. First is the need to demonstrate strong commitment to security reform, politically risky though this may be. The PA also needs to reinvigorate its program of governance reforms in order to create an internal environment more attractive to private investors. Chapter Six lays out an agenda of actions that the Bank believes would lay the basis for economic regeneration. It is further proposed that the donor community track progress by the parties in tackling these key preconditions for economic revival. If significant progress is made against a set of agreed indicators, a major new donor effort would then be justified - and a donor pledging conference should be called.